Kontribusi efikasi diri terhadap kemalasan sosial siswauh efikasi diri terhadap social loafing (kemalasan sosial) pada siswa SMA Plus PGRI Cibinong - Astuti, Rani Fajar; Prasetyaningtyas, Wahyu Eka; Hanifah, Nani (Orien: Cakrawala Ilmiah Mahasiswa, 2024)
the purpose of this study was to see the effect of self-efficacy on social loafing in SMA Plus PGRI Cibinong students. The method used in this research is quantitative method with hypothesis testing using simple linear regression analysis. The population in this study amounted to 314 students, then the sample used was 176 students with simple random sampling technique. The research instruments used were a self-efficacy scale questionnaire and a social loafing scale questionnaire. The results showed that there was an effect of self-efficacy on social loafing in SMA Plus PGRI Cibinong students, where the R Square value was found to be 0.233, which means that the effect of the self-efficacy variable on the social loafing variable was 23.3%, the remaining 76.7% was influenced by other factors outside of the study.